Sensorimotor gating of the startle reflex: what we said 25 years ago, what has happened since then, and what comes next. (November 2016) - Swerdlow, Neal R; Braff, David L; Geyer, Mark A
Our 1992 paper, 'The neural substrates of sensorimotor gating of the startle reflex: a review of recent findings and their implications', reviewed a series of (then) new and preliminary findings from cross-species studies of prepulse inhibition of the startle reflex, and commented on their implications. At the time that the report was composed, PubMed listed about 40 citations for studies using the search term 'prepulse inhibition'. In the ensuing 25 years, the field has added about 2700 such reports, reflecting the substantial growth in interest in prepulse inhibition and its utility across a number of different experimental applications. The 30th anniversary of the Journal of Psychopharmacology provides an opportunity to comment briefly on what was described in that 1992 report, how the field has progressed in the subsequent decades, and the paths forward for studies of prepulse inhibition and its use as an operational measure of sensorimotor gating. Among these future paths, we highlight the use of prepulse inhibition as: an endophenotype for genomic studies, and a biomarker for healthy brain circuitry, which may predict sensitivity to psychotherapeutics. Our 1992 report was highly speculative and based on paper-thin empirical data, yet viewed in a certain light, it appears to have contained a basic roadmap for a journey spanning the next 25 years of prepulse inhibition research… and 'what a long, strange trip it's been'.